Peran Zakat Produktif Dalam Meningkatkan Pendapatan Mustahik Pada BAZNAS Kabupaten Lima Puluh Kota : Studi Kasus Kecamatan Akabiluru Kabupaten Lima Puluh Kota - Anna Fachiratul Ulum; Aidil Alfin (Sharing: Journal of Islamic Economics Management and Business, 2025)
Zakat plays a significant part in mustahik's income; the Fifty Cities BAZNAS provides assistance in the form of both productive and consumptive zakat. The mustahik in the Akabluru District of the Fifty Cities District receive productive zakat assistance from BAZNAS Fifty District Cities. The purpose of this study is to understand a few significant zakat productive contributions with regard to increasing mustahik pay rates. The technique being used is a quantitative method with a fixed point for gathering data through observation, documentation, and interviews. The findings of this study show that productive zakat has been spent in accordance with its designated purposes, but some mustahik continue to use monies for other purposes, such as meeting fundamental requirements. Effective zakat has contributed to rising mustahik income, but when compared to the national income level, mustahik income in Akabiluru District, Lima Puluh Kota Regency is included in the medium income group and there are some mustahik who are included in the high income group.